Second language writing instruction in global contexts English language teacher preparation and development - Seloni, Lisya editor; Henderson Lee, Sarah editor (New perspectives on language and education, 2020)
"This book revisits second language (L2) writing teacher education by exploring the complex layers of L2 writing in non-English dominant contexts (i.e. English as a foreign language contexts). It re-envisions L2 writing teacher education by moving away from uncritical embracement of Western-based writing pedagogies"--